Gender Equality and Labour Force Participation: Mind the Gap. Issue 1 (June 2019) - Banerjee, Madhusree
Despite increase in education, female labour force participation in India is abysmally low and has fallen over the years. The reasons for this are complex and involve a whole range of social and cultural dimensions apart from objective conditions. The article attempts to analyze how social mindset of women being homemakers is one of the reasons that affect this. In addition, lack of education and job-oriented courses, lack of mobility and discrimination at workplace have acted as deterrents for women to come out to the public space for work. Thus, policy which tries to address this gap must be holistic. Legislations alone are not enough, and all stakeholders should join hands to close this gap.